Measuring Macroeconomic Uncertainty Using Internet Search Data: The Case of Poland - Pietrucha, Jacek; Gulewicz, Michał (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Despite extensive discussion, measuring uncertainty – especially macroeconomic uncertainty – remains an open issue. While valuable, traditional data sources may be temporally or spatially limited and may not accurately capture public sentiment or the uncertainty perceived by diverse social groups such as households, especially considering the recent transition from traditional media to electronic. Aim: A new Macroeconomic Uncertainty Index (MUI) for Poland, covering the period from 2004 to 2024 is presented and evaluated. This index utilizes the behavior of economic agents expressed through online search patterns, providing a real-time tool for assessing economic uncertainty. Results: The MUI captures uncertainty perceived by diverse social groups, particularly considering the recent transition from traditional media to electronic channels of information flow. Comparative analysis revealed the unique characteristics of the MUI compared to other uncertainty indicators, such as survey-based and text-based measures, emphasizing the need for multiple metrics to fully capture the multifaceted nature of macroeconomic uncertainty. The MUI provides an alternative to traditional measures, making it especially valuable for studies on public responses to macroeconomic changes.